Victims’ rights are human rights: The importance of recognizing victims as persons - Wemmers Jo-Anne (Temida, 2012)
In this paper the author argues that victims’ rights are human rights. Criminal law typically views victims as witnesses to a crime against the state, thus shutting them out of the criminal justice process and only allowing them in when they are needed to testify. This is a major source of dissatisfaction for victims who seek validation in the criminal justice system. Victims are persons with rights and privileges. Crimes constitute violations of their rights as well as acts against society or the state. While human rights instruments, such as the Universal Declaration of Human Rights, do not mention crime victims specifically, a number of rights are identified, which can be viewed from the victim’s perspective. As individuals with dignity, victims have the right to recognition as persons before the law. However, such rights are only meaningful if they can be enforced.